2022
DOI: 10.1007/s00330-022-08700-y
|View full text |Cite
|
Sign up to set email alerts
|

Probability maps classify ischemic stroke regions more accurately than CT perfusion summary maps

Abstract: Objectives To compare single parameter thresholding with multivariable probabilistic classification of ischemic stroke regions in the analysis of computed tomography perfusion (CTP) parameter maps. Methods Patients were included from two multicenter trials and were divided into two groups based on their modified arterial occlusive lesion grade. CTP parameter maps were generated with three methods—a commercial method (ISP), block-circulant singular value de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In addition, spatial accuracy (Dice) was significantly improved for the logistic model in comparison to the thresholding-based model in our internal cross-validation. This superiority of the multiparametric logistic approach is well in line with a recent study which demonstrated higher predictive performance based on precision-recall plots and mean (but not mean absolute) volume difference [ 7 ]. In our analyses, the improved spatial accuracy did not generalize to the external validation cohort.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In addition, spatial accuracy (Dice) was significantly improved for the logistic model in comparison to the thresholding-based model in our internal cross-validation. This superiority of the multiparametric logistic approach is well in line with a recent study which demonstrated higher predictive performance based on precision-recall plots and mean (but not mean absolute) volume difference [ 7 ]. In our analyses, the improved spatial accuracy did not generalize to the external validation cohort.…”
Section: Discussionsupporting
confidence: 84%
“…After deconvolution and calculation of perfusion parameter maps [ 4 ], individual ischemic core and penumbra are visualized and quantified by thresholding these parameter maps. Established criteria [ 2 , 3 ] are CBF rel (i.e., cerebral blood flow relative to the unaffected hemisphere) < 30% for the ischemic core [ 5 ] and T max (i.e., time-to-maximum of the flow-scaled residue function) > 6 s for the entire hypoperfused area including the ischemic penumbra [ 6 ], although different criteria are also applied in various commercially available software packages [ 7 ]. However, simple thresholding-based methods are not suited to exploit the full potential hidden in the high-dimensional perfusion data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The arterial input function was determined automatically as described elsewhere (14). An in-house developed model-based non-linear regression method generated the perfusion maps of the cerebral blood flow, the cerebral blood volume, the mean transit time, and the time to peak (15). From these perfusion maps, a logistic model (that is described elsewhere) determined the hypoperfused region (i.e., the infarct core and the penumbra taken together) (16).…”
Section: Determining Hypoperfused Regions With Ctpmentioning
confidence: 99%
“…To this day, there is no standardized classification between the different processors to define the core and penumbra, since vendors establish their variations to define infarct cores and penumbras in their software [49]. However, it is the match or mismatch between the CBV and CBF with the MTT and TTP that will determine if the area is a penumbra or infarct core; this means that, if all the variants match on having altered levels, as indicated in Table 2, it is classified as an infarct.…”
Section: Ct Perfusionmentioning
confidence: 99%